A High Reverse Breakdown Voltage p-GaN Gate HEMT with Field Control Drain. (1st August 2022) - Xing, Pengcheng; Wang, Fangzhou; Luo, Pan; Sun, Ruize; Shi, Yijun; Xu, Xinbing; Chen, Yiqiang; Chen, Wanjun
Abstract : In this work, a high reverse blocking voltage ( BV R ) p-GaN gate high electron mobility transistor with field control drain (FCD-HEMT) has been proposed and fabricated. The FCD-HEMT features the field control drain (FCD), consisting of electrically shorted Ohmic contact structure and p-GaN cap. In the OFF-state, the 2-Dimensional Electron Gas (2DEG) channel is cut off due to the p-GaN cap introduced field control, which provides FCD-HEMT with reverse blocking capability. In the ON-state, the re-formed 2DEG channel offers a non-potential barrier pathway for electrons transfer from source to drain and ensures a low resistance of the FCD-HEMT. The fabricated device exhibits 1400 V forward breakdown voltage ( BV F ) and −1240 V reverse breakdown voltage ( BV R ), 12.7 mΩ·cm 2 low specific ON-resistance, and 188 mA mm −1 max drain current while maintaining normally-OFF capability. These results demonstrate the great potential of FCD-HEMTs in 1200 V-class power applications.